Neutrophil-to-lymphocyte, monocyte-to-lymphocyte, and platelet-to-lymphocyte ratios as prognostic markers in canine osteosarcoma: Correlation with cytological and histopathological features - de Almeida Fernandes E Silva, Gabriela [UNESP]; Jimenez, Juliana Jurado [UNESP]; de Moura, Fernanda Barthelson Carvalho [UNESP]; de Souza Gomes, Thays [UNESP]; Ordoñez, Francisco Javier Pedraza; Florez, Luis Mauricio Montoya; Barbisan, Luis Fernando [UNESP]; de Oliveira, Rogerio Antonio [UNESP]; Zambrano, Carlos Mario Gonzalez [UNESP]; Dias-Melicio, Luciane Alarcão [UNESP]; Rocha, Noeme Sousa [UNESP] (Elsevier, 2025)
Canine osteosarcoma is a highly aggressive neoplasm with a complex tumor microenvironment influenced by inflammatory and cytomorphological factors. This study aimed to evaluate the prognostic value of systemic and tumor-associated inflammatory indices, along with cytological and histopathological characteristics, in predicting clinical outcomes. A retrospective cohort of canine osteosarcoma cases was analyzed, assessing the neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR), and platelet-to-lymphocyte ratio (PLR), in addition to cytopathological and histopathological features, as well as NLR values quantified in cytology. The results indicated that early clinical intervention significantly improved postoperative survival, reinforcing the importance of timely diagnosis. Both NLR and LMR showed significant correlations with tumor progression and prognosis, supporting their utility as continuous monitoring tools Tumor-associated NLR was linked to neutrophilic infiltration and osteoid content, suggesting involvement of the inflammatory response in tumor progression. Moreover, tumor-associated NLR inversely correlated with overall and postoperative survival times, supporting its association with tumor aggressiveness beyond cytological and histological features. Cytological and histopathological analyses highlighted nuclear pleomorphism and cellular density as potential malignancy indicators, supporting cytology as an accessible and cost-effective diagnostic tool. High vascular involvement was observed, reinforcing the hypothesis of a pro-angiogenic microenvironment contributing to tumor invasiveness. These findings emphasize the translational relevance of inflammatory indices and cytomorphological parameters in veterinary oncology, providing insights into tumor biology and potential therapeutic stratification strategies. Further studies are required to refine these biomarkers and integrate them into clinical protocols and comparative oncology research.